Acute effects of ammonia on 'citirulline- no cycle enzymes', arginase and related metabolites in different regions of rat brain - Swamy, Mummnedy (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Nitric oxide (NO) is involved in numy physiological and pathological processes in the brain. NO is synthesized frmn arginine by nitric oxide synthase (NOS) enzytnes. Citru11ine, which is fonned as a by-product. of the NOS reaction, can he recycled to arginine by successive actions of argininosuccinnte synthetase (ASS) nnd argininosuccinate lyase (ASL) via the citrulline-NO cycle. llypermnn1onetnia is kno\vn to cause poorly understood perturbations of the citrulline-NO cycle. Both ASS and ASL genes at·e reported to he induced in nstrocytes hut not in neurons of nggrcgates exposed to 5 mM arnn1oniun1 chloride, suggesting that hyperan1n1onen1ic hrain n1ight increase its recycling of citrulline to arginine. To understand the role of citntlline-NO cycle in hyperanltnonetnia, NOS, ASS, ASL and arginase activities, as well as nitrate/nitrite (NOx), the stable end products of NO, nnd other related tnetabolites were estin1ated in cerebral cortex (CC), cerebelltun (CB) and brain stenl (BS) of rats subjected to acute ammonia toxicity (0.8n11nol of an11nonhun acetate per I OOg hody weight). N()x concentration and NOS activity were found to increase in all the regions of brain in acute amn1onia toxicity. The activities of ASS (CC. CB and BS) and ASL (CC and CB) also showed an increase whereas the activity of arginase was not clmngcd. The concentrations of arginine and ornithiue were increr.sed in nil the regions of hrain in acute mnrnonia toxicity whereas citrulline concentration was not changed. Glutatnine concentration was significantly increased in all regions of brain while glutatnate and GABA concentrations were not changed. The results of this study clearly demonstrated the increased formation of NO, suggesting the involvernent of NO in the pathophysiology of acute am1nonia toxicity. The increased activities of ASS and ASL enzymes indicate the increased and effective recycling of citrulline to arginine in acute mnn1onia toxicity, 111aking NO production more effective and contributing to its toxic effects.